KORELASI KEBIASAAN MEMBACA MANGA DENGAN KEMAMPUAN KANJI PADA MAHASISWA BAHASA JEPANG UNIVERSITAS NEGERI PADANG - Annisa Rahmawati; Maulluddul Haq (Universitas Negeri Padang, 2022)
This study aims to see how strong the relationship between reading manga habits and students' kanji abilities is. The design of this study is a correlation design. The population in this study amounted to 100 students. The sampling technique used in this study was purposive sampling with a sample of 80 students. This study uses a questionnaire to see the habit of reading manga and a test to determine the students' kanji ability. The results of this study are: First, the average value of students' habits in reading manga is 77.33. Second, the students' kanji ability is 82.25. Third, the correlation coefficient of the two variables; manga reading habit and kanji ability is 0.784. Thus, the researcher proves that is rejected and is accepted, meaning that there is a significant relationship between students' habits in reading manga and students' kanji abilities.